ANALISIS KONTRASTIF DALAM PEMBELAJARAN BAHASA ARAB - Enok Rohayati (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah, 2018)
The succesfull teaching not only depend on the teaching materials, but also on the teaching methods. Therefore, the Arabic teachers require teaching skills. Moreover, the Indonesian student assumes the existence of the difficulties anywhere in the Arabic learning. There is evidence that the Arabic teaching-learning process as a foreign language meets a serious problems. The most problems caused by defferencies between bahasa Indonesia as a native language and the Arabic as a target language. Robert Lado states that the differences between native and target language cause difficulties. In contrast, a similarities between two languages will be a fasilitsion in the Arabic learning. This contrastive study tries to analyse the differences between Arabic and bahasa Indonesia. The main concussion of this study shows that differences between two language require the Arabic teacher who knows the contrastive analysis, so that he can eliminate the Arabic learning Problems.